Reconfiguration of the proteasome during chaperone-mediated assembly - Park, Soyeon; Li, Xueming; Kim, Ho Min; Singh, Chingakham R.; Tian, Geng; Hoyt, Martin A.; Lovell, Scott; Battaile, Kevin P.; Zolkiewski, Michal; Coffino, Philip; Roelofs, Jeroen; Cheng, Yifan; et al. (My University, 2014)
The proteasomal ATPase ring, comprising Rpt1-Rpt6, associates with the heptameric α ring of the proteasome core particle (CP) in the mature proteasome, with the Rpt C-terminal tails inserting into pockets of the α ring[superscript 1-4]. Rpt ring assembly is mediated by four chaperones, each binding a distinct Rpt subunit[superscript 5-10]. We report that the base subassembly of the proteasome, which includes the Rpt ring, forms a high affinity complex with the CP. This complex is subject to active dissociation by the chaperones Hsm3, Nas6, and Rpn14. Chaperone-mediated dissociation was abrogated by a nonhydrolyzable ATP analog, indicating that chaperone action is coupled to nucleotide hydrolysis by the Rpt ring. Unexpectedly, synthetic Rpt tail peptides bound α pockets with poor specificity, except for Rpt6, which uniquely bound the α2/α3 pocket. Although the Rpt6 tail is not visualized within an α pocket in mature proteasomes[superscript 2-4], it inserts into the α2/α3 pocket in the base-CP complex and is important for complex formation. Thus, the Rpt-CP interface is reconfigured when the lid complex joins the nascent proteasome to form the mature holoenzyme.
Keywords: Proteasome; Chaperone; Single particle cryoEM; ATPase